Pulmonary Hypertension in the Newborn GTP-Cyclohydrolase 1-Deficient Mouse - Belik, Jaques (Free Radic Biol Med, 2011)
Tetrahydrobiopterin (BH4) is a regulator of endothelial nitric oxide synthase (eNOS) activity. Deficient levels result in eNOS uncoupling with a shift from nitric oxide (NO) to superoxide generation. The hph-1 mutant mouse has deficient GTP-cyclohydrolase 1 (GTPCH1) activity resulting in low BH4 tissue content. The adult hph-1 mouse has pulmonary hypertension, but whether such condition is present from birth is not known. Thus, we evaluated newborn animals’ pulmonary arterial medial thickness, biopterins content (BH4+BH2), H(2)O(2) and eNOS, right ventricle-to-left-ventricle+septum ratio (RV/LV+septum) and near-resistance pulmonary arteries agonist-induced force and endothelium-dependent and-independent relaxation. The biopterins lung content was inversely related to age for both types, but significantly lower in hph-1 mice, as compared to wild-type animals. As judged by the RV/LV+septum newborn hph-1 mice have pulmonary hypertension and following a two-week 13% oxygen exposure the ratio was similar in both types. The pulmonary arterial agonist-induced force was reduced (P<0.01) in hph-1 animals and no type-dependent difference in endothelium-dependent or –independent vasorelaxation was observed. When compared to wild-type mice, the H(2)O(2) lung content was increased, whereas the eNOS expression decreased (P<0.01) in hph-1 animals. The pulmonary arterial medial thickness, a surrogate marker of vascular remodeling was increased (P<0.01) in hph-1 compared to wild-type mice. In conclusion, our data suggest that pulmonary hypertension is present from birth in the GTPCH1 deficient mice, not as a result of impaired vasodilation, but secondary to vascular remodeling.